Religious Moderation: The Concepts and Implementation of Local Traditions in Karimunjawa - Rohmatul Faizah; Jihan Avie Yusrina; Ahmad Baedowi (Jurnal Dialog, 2022)
This research is encouraged by the emergence of social friction due to different perspectives on religious issues in Indonesia. Some people clash religion with cultural rituals such as sedekah laut. At the same time, the others reject leaders from different religions and even desire to change the ideology into a caliphate system. Therefore, it is necessary to have a moderate attitude towards religion to create a peaceful and harmonious life. This condition can be found in Karimunjawa, where various ethnicities and religions live together but integrate to form a harmony. Thus, this research reveals the concept of religious moderation in Karimunjawa and how it is implemented through local traditions. The research problem was addressed through qualitative research using a case study approach. The results show that, although most Karimunjawa people do not possess a well-established theoretical understanding of the religious moderation concept, the practice of such concept can be observed in their everyday life. The implementation of moderation values ​​is carried out from one generation to another through acculturation of local wisdom ​​and religious values, such as in the barikan kubro, mudunke kapal, kumpulan, and sambatan. So far, there have been no obstacles in implementing religious moderation because it has become part of the tradition. Keywords: religious moderation, local tradition, Karimunjawa